KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN KEMITRAAN DENGAN ALUMNI UNTUK MENDUKUNG MUTU PEMBELAJARAN DI SEKOLAH MENENGAH PERTAMA: Studi Kasus di SMP Negeri 1 Darangdan Kabupaten Purwakarta - Supyan Sauri; Andi Saleh; Dian Mardia; Dian Rini Handayani; Iis Kurniawati; Lilih Nurmilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning quality is one of the primary indicators of educational success. School principals are expected to implement adaptive and collaborative leadership while strengthening partnerships with various stakeholders to improve learning quality. One of the strategic stakeholders is the alumni association. Alumni possess valuable professional experience, social capital, financial resources, and extensive networks that can significantly contribute to school development. Nevertheless, in many schools alumni involvement remains incidental and has not yet become an integral component of educational quality improvement. This study aims to analyze the principal's leadership in developing partnerships with alumni to support learning quality improvement at SMP Negeri 1 Darangdan, Purwakarta Regency. The study adopts Peter Senge's Learning Organization Theory, emphasizing five organizational disciplines: personal mastery, mental models, shared vision, team learning, and systems thinking. A qualitative case study approach is employed. Data are collected through interviews, observations, and document analysis involving the principal, teachers, alumni representatives, school committee members, and other stakeholders. Data are analyzed using data reduction, data display, conclusion drawing, and triangulation techniques to ensure validity. The expected findings describe leadership strategies in establishing sustainable alumni partnerships, forms of alumni participation in improving instructional quality, supporting and inhibiting factors, and recommendations for strengthening collaborative school governance. The study is expected to contribute to educational leadership studies and provide practical recommendations for strengthening alumni engagement in improving educational quality